2018
DOI: 10.1038/s41375-018-0252-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting quiescent leukemic stem cells using second generation autophagy inhibitors

Abstract: In chronic myeloid leukemia (CML), tyrosine kinase inhibitor (TKI) treatment induces autophagy that promotes survival and TKI-resistance in leukemic stem cells (LSCs). In clinical studies hydroxychloroquine (HCQ), the only clinically approved autophagy inhibitor, does not consistently inhibit autophagy in cancer patients, so more potent autophagy inhibitors are needed. We generated a murine model of CML in which autophagic flux can be measured in bone marrow-located LSCs. In parallel, we use cell division trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 44 publications
6
86
0
Order By: Relevance
“…Mice lacking FOXO3A show abnormally high ROS levels, impaired leukaemia initiating capacity and myeloproliferation . Similarly, recent results from in vivo studies indicate that potent lysosomal inhibition drives LSCs out of quiescence leading to an expansion of myeloid progenitors . In addition, these results are in line with previous studies in normal HSCs, showing that autophagy deficiency increases oxidative stress and rapidly reduces the stem cell pool .…”
Section: Role and Regulation Of Autophagy In CML And Lscssupporting
confidence: 87%
See 4 more Smart Citations
“…Mice lacking FOXO3A show abnormally high ROS levels, impaired leukaemia initiating capacity and myeloproliferation . Similarly, recent results from in vivo studies indicate that potent lysosomal inhibition drives LSCs out of quiescence leading to an expansion of myeloid progenitors . In addition, these results are in line with previous studies in normal HSCs, showing that autophagy deficiency increases oxidative stress and rapidly reduces the stem cell pool .…”
Section: Role and Regulation Of Autophagy In CML And Lscssupporting
confidence: 87%
“…In CML, the expression of ATG genes has been shown to be upregulated in more primitive populations compared to more mature cells . In line with this, our results obtained from leukaemic mice expressing GFP‐LC3 revealed that LSCs have higher autophagy levels compared to more differentiated cells . Similarly, Warr et al .…”
Section: Role and Regulation Of Autophagy In CML And Lscssupporting
confidence: 86%
See 3 more Smart Citations